420 Transcriptome analysis of glassy cell carcinoma and mucinous adenocarcinoma compared with squamous cell carcinoma of uterine cervix. (13th November 2020) - Ishizuka, Y; Hasebe, R; Asano, H; Sakurai, M; Yamazaki, H; Ihira, K; Endo, D; Mitamura, T; Konno, Y; Kato, T; Kudo, M; Watari, H; et al.
Abstract : Objectives: Cervical cancer is the fourth leading cause of cancer mortality in women worldwide. Most of cervical cancer are squamous cell carcinoma (SCC), and the standard therapy has developed in SCC. However, therapeutic strategy for minor histological types, such as glassy cell carcinoma (GCC) and mucinous adenocarcinomas intestinal type (Muc) have not yet been established. In this study, we aimed to characterize GCC and Muc compared with SCC by transcriptome analysis. Methods: Cancer tissues before treatment were kept in RNA later® immediately after resections, and frozen in -80 centi-degrees until analysis. Total RNAs were extracted by TRIZOL and cDNA library was constructed by SureSelect Strand-Specific RNA library Kit (Agilent). Sequencings were performed by HiSeq2500 (Hiseq SR Rapid Cluster Kit v2, Illumina). Results: We performed RNA sequencing for 10 cervical cancers including 6 SCC, 2 adenocarcinomas usual type (Adeno), 1 Muc, and 1 GCC. Both GCC and Muc were infected by HPV 18, and FIGO stage were IB2 and IIA1, respectively. GCC patient showed poor survival but Muc patient was alive without recurrence. In comparison with SCC, the number of up-and down-regulated genes (5 Fold change) was 1456 and 3326 in GCC, while 877 and 1203 in Muc, respectively. Gene ontology analysis revealed that glycoprotein hormones in GCC and HNF3A pathway in Muc were found to be activated. Conclusions: Specific pathways may be activated in each histological type. Further analysis may provide specific markers for diagnosis and/or prognosis in minor histological type of cervical cancer.